COVID-19 stigma and depression across race, ethnicity and residence. (21st April 2023) - Rahman, Rahbel; Azhar, Sameena; Wernick, Laura J.; Huang, Debbie; Maschi, Tina; Rosenblatt, Cassidy; Patel, Rupal
ABSTRACT: Our cross-sectional study seeks to understand how COVID-19 stigma, race/ethnicity [Asian, Black, Hispanic/Latinx, white] and residency [New York City (NYC) resident vs. non-NYC resident] associated with depression. Our sample includes 568 participants: 260 (45.77%) were NYC residents and 308 (54.3%) were non-NYC residents. A series of multiple linear regression were run to examine the relationship between race/ethnicity, COVID-19 stigma, and depressive symptoms. Irrespective of residency, older age and ever being diagnosed with COVID-19 were negatively associated with depressive symptoms. Stigma and thinking less of oneself significantly associates with depressive symptoms across residency. Our study expects to benefit mental health care providers and public health professionals in designing best practices to mitigate stigma in ongoing or future pandemics.